Encapsulation of anthocyanins in black bean (Phaseolus vulgaris) extracts using spray-drying and their stability under various pH and temperature processing conditions - Onsaard, Ekasit; Onsaard, Wiriya (Agriculture and Natural Resources, 2023)
Importance of the work: Anthocyanins from black beans are a natural pigment providing health benefits to consumers; however, they are heat- and pH-sensitive compounds during food processing. Objectives: To stabilize anthocyanins in black beans under food processing conditions using microencapsulation techniques with a suitable, low-cost wall material. Materials & Methods: Black bean extracts were mixed with maltodextrin of dextrose equivalent (DE) 10 and 15. The encapsulation process was conducted at various spray-drying temperatures. The stability of the bioactive compounds in the pigment powders was observed by solubilizing in a buffer solution with a pH range of 3–9 under different heat treatments. Results: The levels of anthocyanins and phenolic compounds in the black bean powders decreased with increasing air-drying temperature (180–210°C) and DE value (from DE10 to DE15). However, the physical properties and antioxidant activities measured using the 2,2-diphenyl-1-picrylhydrazyl and 2-2’-azino-bis (3-ethyl-benzothiazoline-6-sulfonic acid) diammonium salt methods were not significantly different among the drying conditions. The bioactive compounds and antioxidant activities were more stable in the encapsulated pigment powders for a broad pH range of the buffer solution, based on pasteurization compared to sterilization. The pigment powder encapsulated with the higher DE value of maltodextrin provided a lower content of bioactive compounds; however, the antioxidant activities were stabilized under pasteurization. Main finding: The stability was highest for the bioactive compounds and antioxidant activities in black bean powders encapsulated with low DE maltodextrin using an air-drying temperature below 200°C when solubilized in buffer solutions over a pH range of 3–7 due to the co-pigment affect. This powder could be used as a functional ingredient for the food and pharmaceutical industries for a range of pH conditions.